Pre-existing cell populations with cytotoxic activity against SARS-CoV-2 in people with HIV and normal CD4/CD8 ratio previously unexposed to the virus - Casado-Fernández, Guiomar; Cantón, Juan; Nasarre, Laura; Ramos-Martín, Fernando; Manzanares, Mario; Sánchez-Menéndez, Clara; Fuertes, Daniel; Mateos, Elena; Murciano-Antón, María Aranzazu; Pérez-Olmeda, Mayte; Cervero, Miguel; Torres, Montserrat; et al. (Frontiers in Immunology, 2024)
HIV-1 infection may produce a detrimental effect on the immune response. Early start of antiretroviral therapy (ART) is recommended to preserve the integrity of the immune system. In fact, people with HIV (PWH) and normal CD4/CD8 ratio appear not to be more susceptible to severe forms of COVID-19 than the general population and they usually present a good seroconversion rate in response to vaccination against SARS-CoV-2. However, few studies have fully characterized the development of cytotoxic immune populations in response to COVID-19 vaccination in these individuals. In this study, we recruited PWH with median time of HIV-1 infection of 6 years, median CD4/CD8 ratio of 1.0, good adherence to ART, persistently undetectable viral load, and negative serology against SARS-CoV-2, who then received the complete vaccination schedule against COVID-19. Blood samples were taken before vaccination against COVID-19 and one month after receiving the complete vaccination schedule. PWH produced high levels of IgG against SARS-CoV-2 in response to vaccination that were comparable to healthy donors, with a significantly higher neutralization capacity. Interestingly, the cytotoxic activity of PBMCs from PWH against SARS-CoV-2-infected cells was higher than healthy donors before receiving the vaccination schedule, pointing out the pre-existence of activated cell populations with likely unspecific antiviral activity. The characterization of these cytotoxic cell populations revealed high levels of T cells with degranulation capacity against SARS-CoV-2-infected cells. In response to vaccination, the degranulation capacity of CD8+ T cells also increased in PWH but not in healthy donors.The full vaccination schedule against COVID-19 did not modify the ability to respond against HIV-1-infected cells in PWH and these individuals did not show more susceptibility to breakthrough infection with SARS-CoV-2 than healthy donors after 12 months of follow-up. These results revealed the development of protective cell populations with broad-spectrum antiviral activity in PWH with normal CD4/CD8 ratio and confirmed the importance of early ART and treatment adherence to avoid immune dysfunctions.